The use of WhatsApp and Quizizz in higher education during Covid-19 pandemic: EFL students’ perspectives - Nurliana - Nurliana (English Department - University of Sultan Ageng Tirtayasa, 2022)
WhatsApp and Quizizz were used for English online learning during Covid-19 pandemic in three English classes of Islamic education department at IAIN Palangka Raya in Academic Year 2019/2020. The use of WhatsApp and Quizizz as the learning media for English online learning was important to be evaluated in order to reveal the advantages and disadvantages of those media by allowing the students to give their perspectives on the use of those media since they have concrete experience of using those media. Moreover, there were still no research reports that had been published regarding the perspectives of the EFL students in higher education on the use of WhatsApp and Quizizz as the learning media for English online learning during Covid-19 pandemic. Therefore, this research aimed to investigate the perspectives of the EFL students in higher education on the use of WhatsApp and Quizizz as the learning media for English online learning during Covid-19 pandemic. This research was designed as a qualitative survey research. The participants of this research were 102 second semester students from three English classes of Islamic education department at IAIN Palangka Raya in Academic Year 2019/2020. The result of this research showed that the students gave positive response on the use of WhatsApp and Quizizz as the learning media for English online learning during Covid-19 pandemic. It could be inferred that WhatsApp and Quizizz were the appropriate learning media to support English online learning process in higher education during Covid-19 pandemic